Remifentanil infusion versus propofol and remifentanil patient controlled sedation/analgesia for moderate sedation during interventional radiological procedures: A prospective randomized trial (Annals of Medical Research, 2021)
None
Keywords: Remifentanil; propofol; sedation; interventional radiology